Allele and genotype frequencies of variants in P450 cytochromes, transports, and DNA repair enzymes in the Dominican Republic population - Pérez-Duval, Elizabeth; Calderón, Berniza; Izquierdo, Marlen; Herrera-Isidrón, José A.; Reyes-Reyes, Elizabeth; Herrera, Alejandro; Soto, Manuel; Beltré, Alba; Rodeiro-Guerra, Idania (Frontiers in Pharmacology, 2025)
IntroductionSingle-nucleotide variants (SNVs) give rise to important inter-individual and inter-ethnic variabilities in the metabolism and disposition of several therapeutic agents and may cause differences in the treatment response to clinically important drugs like antiarrhythmics, antidepressants, antihistamines, and antipsychotics, among others. Information about the prevalence of variants in the Dominican Republic population is still limited. The aim of this study was to describe the frequency distribution of 32 SNVs from 14 genes with pharmacogenetic interest within a sample of 150 unrelated healthy individuals.MethodsGenotype and allele frequencies were determined, and pairwise Wright’s FST statistic was evaluated.ResultsHardy–Weinberg equilibrium deviations were found in seven loci from CYP2D6 (rs16947, rs3892097, rs1058164, rs1135840, and rs28371725) and CYP2C19 (rs12769205 and rs4244285) genes. The minor allele frequencies ranged from 0.01 to 0.50 values in the xenobiotic biotransformation enzymes and transporter genes. The average admixture estimates were 51.6%, 39.5%, and 8.9% for European, African, and Amerindian ancestries, respectively. Pairwise FST analysis revealed that Dominicans displayed genetic similarity to Latin American populations, especially those with Afro-Caribbean ancestry, given the selected variants. Higher differences were identified from East and South Asians, Europeans, and Africans, in which several values above the FST threshold for moderate differentiation were identified within variants in CYP2C, CYP3A, CYP1A1, ABCB1, SLC45A2, XRCC1, and XRCC3 genes.ConclusionsThese results should allow establishing the clinical relevance of pharmacogenetic testing in variant alleles related to drug transport and metabolism genes in this population.